Convergent calculations of positron scattering from molecular hydrogen - Zammit, M.; Fursa, Dmitry; Bray, I. (2015)
An overview is given of the recently developed adiabatic-nuclei convergent closecoupling method for positron-molecule scattering. Fixed-nuclei single-centre calculations of positron-H2 scattering are presented. Particular emphasis is given to demonstrating convergence with increasing size of the basis and the projectile partial-wave expansion. Results are converged to within ±5%.